TEACHERS’ PERCEPTIONS ON THE USE OF ICT IN INDONESIAN EFL LEARNING CONTEXT - Sophia Fithri Al-Munawwarah (University of Kuningan, 2014)
Abstract: This study aims to investigate teachers’ perceptions towards the implementation of ICT in EFL teaching and learning process. The present study applied descriptive qualitative method, and the data were collected through open-ended questionnaire and interview to gain relevant data. The results of the present study were in line with the previous findings from the studies conducted by Park Son (2009); Barnawi (2009); and others. The research findings of the present study discovered that there were three benefits of using ICT in English teaching and learning process; namely, helping the teachers to conduct interesting and enjoyable learning activities, promoting learner autonomy, and motivating the students to learn. The present study also reveals some challenges encountered by the teachers in using ICT in EFL classes and strategies to overcome the challenges. Overall, the teachers’ perceptions towards the utilization of ICT in English teaching were positive. Thus, it is recommended to use ICT in English teaching and learning process.Keywords: English language teaching, ICT, teachers’ perceptions.